2019
DOI: 10.1073/pnas.1816254116
|View full text |Cite
|
Sign up to set email alerts
|

Relapse-associated AURKB blunts the glucocorticoid sensitivity of B cell acute lymphoblastic leukemia

Abstract: Glucocorticoids (GCs) are used in combination chemotherapies as front-line treatment for B cell acute lymphoblastic leukemia (B-ALL). Although effective, many patients relapse and become resistant to chemotherapy and GCs in particular. Why these patients relapse is not clear. We took a comprehensive, functional genomics approach to identify sources of GC resistance. A genome-wide shRNA screen identified the transcriptional coactivators EHMT2, EHMT1, and CBX3 as important contributors to GC-induced cell death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 71 publications
3
37
0
Order By: Relevance
“…Moreover, suppression of Aurora B enhances the efficacy of radiotherapy 28,29 and overcomes acquired resistance in EGFR targeting therapy 30 . In addition, overexpression of Aurora B causes relapse of B cell acute lymphoblastic leukemia and blunts the glucocorticoid sensitivity 31 . Here, we found that Aurora B is highly expressed in human OSCC tumor tissues and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, suppression of Aurora B enhances the efficacy of radiotherapy 28,29 and overcomes acquired resistance in EGFR targeting therapy 30 . In addition, overexpression of Aurora B causes relapse of B cell acute lymphoblastic leukemia and blunts the glucocorticoid sensitivity 31 . Here, we found that Aurora B is highly expressed in human OSCC tumor tissues and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the A549 lung carcinoma/HepG2 HCC cell model for AhR gene reporter plasmid expression [ 64 ] , applied TGFβ1 results in activation of z , x -plane transcription-ready plasmid upon endogenous TGIF1 transcription at P eff 0.080 as the SMAD co-adapter is required for RNA polymerase transcription, however without the need for applied TGFβ1 in A549 cells that demonstrate a bidirectional negative expansion Δ C micro response P eff of 0.080 as compared the nadir for HepG2 cells, which would between P eff 0.130 ( LGAL1 ) and 0.106 ( UGT1A1 ). The in vitro application of aldosterone (Ald) to SkBr3 mammary carcinoma and tumor-associated endothelial cells results in the transcriptional overactivation of GPER1 (GPR30; P eff 0.376) and SLC9A1 (NHE-1, P eff 0.167) [ 130 ] , and will result in an increase in GR expression concomitantly ( NR3C1 , P eff 0.376) ( Table 10 ), with an increase in pEGFR/ERK1,2 levels as part of the negative C micro expansion response phase, as will occur with application of a combination of E 2 and inverse agonist(s) [ 131 ] with a resultant equivalent increase in intracellular pressure to P eff 0.112 at which CYP11B2 (Ald Synthase) transcription increases at P eff during Δ C micro contraction; whereas, the in vivo application of Dex (~Corticosterone) to normal adrenocortical cells results in a 0.5x-fold decrease in CYP11B1 (11-β-hydroxylase; P eff 0.099) decrease at duration at P eff while an increase with ACTH [ 132 ] , while GABPA ( P eff 0.494) and TSPAN14 ( P eff 0.057) increase in duration at P eff during maintained sensitivity to Dex at CM GR in human B-cell ALL in a viro-transformed cell type [ 133 ] , which reaffirms P eff 0.057 as the maximum lower limit of the contraction-negative P eff C micro expansion response to positive P eff regulation away from P eff 0.088 ( Ighm ) [ 37 ] , 0.088 ( Ighm ) and 0.075 ( Ighg3 ) [ 134 ] . Since the maximum P eff C micro contraction-expansion response to Dex is at the lower limit of cell expansion P eff and equivalent to the Δ C micro response applied co -, ortho -planar PCB-153, this implies GRE and TRE site-tuned parallel pathway involvement (ie CAR, AR), as there is known GR · half-site GRE enhancement of THRB gene transcription [ 135 ] with the potential for JUN (FOS) recruitment of GR to half-site TRE [ 89 ] and regulation of DIO1 ( P eff 0.236) gene transcription at P...…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism(s) by which SUMOylation influences TF binding/occupancy on chromatin have remained uncovered. In this work, by using chromatin immunoprecipitation with selective isolation of chromatin-associated proteins (ChIP-SICAP) and mass spectrometry (MS) from cells stably isotopically-labeled with amino acids in culture (SILAC) ( 18 ), we firstly uncover the composition of the chromatin protein network around the hormone-bound GR, which markedly overlaps with the factors important for the growth of B-ALL cells ( 19 ). Secondly, we show that the protein network is modulated by the SUMOylation status of GR.…”
Section: Introductionmentioning
confidence: 99%